Retraction Notice: Cytotoxic Activities of Ethanolic Crude Extracts from Fruiting Bodies of Bamboo Mushrooms (Dictyophora spp.) Against Cholangiocarcinoma Cells - Chantree, Pathanin; Chumkiew, Sirilak; Jamklang, Mantana; Martviset, Pongsakorn (Asian Medical Journal and Alternative Medicine, 2022)
The article has been retracted at the request of the author.